Laparoscopic vs open approach for transverse colon cancer. A systematic review and meta-analysis of short and long term outcomes. (May 2017) - Athanasiou, Christos D.; Robinson, Jonathan; Yiasemidou, Marina; Lockwood, Sonia; Markides, Georgios A.
Abstract: Background: Transverse colon malignancies have been excluded from all randomized controlled trials comparing laparoscopic against open colectomies, potentially due to the advanced laparoscopic skills required for dissecting around the middle colic vessels and the associated morbidity. Concerns have been expressed that the laparoscopic approach may compromise the oncological clearance in transverse colon cancer. This study aimed to comprehensively compare the laparoscopic (LPA) to the open (OPA) approach by performing a meta-analysis of long and short term outcomes. Methods: Medline, Embase, Cochrane library, Scopus and Web of Knowledge databases were interrogated. Selected studies were critically appraised and the short-term morbidity and long term oncological outcomes were meta-analyzed. Sensitivity analysis according to the quality of the study, type of procedure (laparoscopic vs laparoscopically assisted) and level of lymphadenectomy was performed. Statistical heterogeneity and publication bias were also investigated. Results: Eleven case control trials (1415 patients) were included in the study. There was no difference between the LPA and the OPA in overall survival [Hazard Ratio (HR) = 0.83 (0.56, 1.22); P = 0.34], disease free survival (p = 0.20), local recurrence (p = 0.81) or distant metastases (p = 0.24). LPA was found to have longer operative time [Weighted mean difference (WMD) = 45.00 (29.48, 60.52); P < 0.00001] with earlier establishment of oral intake [WMD = −1.68 (−1.84, −1.53); P < 0.00001] and shorter hospital stay [WMD = -2.94 (−4.27, −1.62); P = 0.0001]. No difference was found in relation to anastomotic leakage (p = 0.39), intra-abdominal abscess (p = 0.25), lymph nodes harvested (p = 0.17). Conclusions: LPA seems to be safe with equivalent oncological outcomes to OPA and better short term outcomes in selected patient populations. High quality Randomized control trials are required to further investigate the role of laparoscopy in transverse colon cancer. Highlights: 11 studies comparing the open to the laparoscopic approach were pooled. The laparoscopic approach carries significant short term benefits with the same disease free and overall survival. Laparoscopic high tie of the middle colic vessels appears to be a safe and feasible technique.